From CSR to Impact; How to Integrate CSR in a University Strategy - Erna Maters; Joke Luttik (Journal of Sustainability Perspectives, 2023)
Wageningen University & Research (WUR) has a Corporate Social Responsibility (CSR) agenda, which was drawn up in 2020, after the adoption of the Strategic Plan. The topic “Research and education to contribute to societal challenges” is at the top of the CSR agenda, because we assume that WUR will have the greatest societal impact through its education and research activities. CSR is all about Impact and impact is a key term in the current strategy. Because CSR, Impact and Strategy are so closely related, especially in a university, it is important to develop new perspectives on how CSR can best be integrated into the strategy. This fits in well with WUR as an organization with a great social responsibility: at an organization like WUR you would expect CSR to be anchored in the core of the organization, so that no separate CSR strategy is needed. The article explores the various ways to embed the CSR perspective in the new Strategic Plan of the organization, describes the strengths and weaknesses of the various approaches and concludes which approach would be the most suitable for a future-proof sustainable university.